1967
DOI: 10.1103/physrev.155.896
|View full text |Cite
|
Sign up to set email alerts
|

Optical Absorption Spectra of the Alkali Halides at 10°K

Abstract: The absorption spectra of all the alkali halides except LiF and Lil, measured in the range 5.0 to 12.0 eV at 10°K, are presented. These data complement earlier measurements made at 80°K. Identification of exciton lines involving d-like electrons is made by a comparison of the crystal absorption and the absorption spectra of rare-gas atoms. From the positions of exciton states with d-like electrons, the energy of the second conduction band at T is deduced for some of the alkali halides. The results of these ded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
45
0
1

Year Published

1970
1970
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(57 citation statements)
references
References 19 publications
11
45
0
1
Order By: Relevance
“…The longitudinal exciton branch has a very similar dispersion to that of the transverse exciton and is nearly independent of k near the Brillouin zone center. In conventional OP absorption measurements, the spectral profiles are dominated by the reflection losses in the stopgap region, which are quite often ignored even though they can introduce significant spectral shifts [22][23][24] [9]. OP measurements of CsBr thin films have been reported for pressures up to 3 kbar at room temperature [25].…”
Section: Introductionmentioning
confidence: 99%
“…The longitudinal exciton branch has a very similar dispersion to that of the transverse exciton and is nearly independent of k near the Brillouin zone center. In conventional OP absorption measurements, the spectral profiles are dominated by the reflection losses in the stopgap region, which are quite often ignored even though they can introduce significant spectral shifts [22][23][24] [9]. OP measurements of CsBr thin films have been reported for pressures up to 3 kbar at room temperature [25].…”
Section: Introductionmentioning
confidence: 99%
“…At slightly higher energies, excitons associated with p-like valence levels and d-like conduction levels are found (d-excitons). It is suggested that the d-excitons, which are very close to the absorption edge in Cs halides (Teegarden & Baldini, 1967) have deformation potential constants with signs opposite to the corresponding constants of the s-excitons, giving rise to a piezo-optic behaviour opposite to that found in K and Rb halides.…”
Section: Discussionmentioning
confidence: 99%
“…The first peak close to the absorption edge is unambiguously assigned to an exciton associated with the highest valence band F~-and the lowest conduction level F6 +, at K=0 in the BZ. [For the assignments of the remaining peaks, see Teegarden & Baldini (1967).] The discussion in this paper will be confined mainly to the first exciton peak.…”
Section: The Absorption Spectrum and Deformation Potential Constantsmentioning
confidence: 99%
See 1 more Smart Citation
“…После основополагающей работы [11] были осуществ-лены прецизионные исследования спектров поглощения и отражения всех ЩГК в широком диапазоне темпе-ратур начиная от 10 K, а с помощью дисперсионных соотношений Крамерса−Кронига из спектров отражения монокристаллов были вычислены спектры оптических констант (см., например, [36][37][38][39][40][41][42]). Было показано, что полосы низкоэнергетических экситонов имеют форму асимметричного лоренциана, характерного для свобод-ных экситонов.…”
Section: международная школа-семинар "unclassified